Incidental Finding of Renal Oncocytoma in a Patient With Agent Orange Exposure. (21st September 2018) - Reddy, Amit; Sessums, Mary; Manucha, Varsha; Henegan, John
Abstract: Introduction: More than 3 million veterans during the Vietnam War had exposure to Agent Orange (AO), an herbicide containing dioxin linked to increased cancer risk. There is an association between AO and hematological disorders, but only a few cases have been reported in relation to renal neoplasms. We present a case of right-sided renal oncocytosis (RO) with AO exposure in a patient with chronic kidney disease (CKD). Case Report: A 68-year-old white male with hypertension, CKD, and previous AO exposure was noted to have serum creatinine 1.9 mg/dL and blood urea nitrogen 36 mg/dL. There was no recent hematuria, flank pain, or weight loss. Renal ultrasound showed multiple renal masses, and MRI confirmed these to be concerning for renal cell carcinoma with one mass upper pole of the right kidney (3.3 cm) and second mass interpolar region of the left kidney (2.3 cm). All nodules were confined to kidney. Preoperative germline testing of a panel of genes in which variants are associated with hereditary renal carcinoma syndromes revealed no pathogenic mutations. Right partial nephrectomy was performed, which noted multiple oncocytic nodules ranging from a microscopic collection of a few cells to large, grossly visible nodules. Immunostains were negative for AMACR and CK7 and positive for CAM5.2 and CD117, consistent with a diagnosis of RO. Discussion: RO—multiple oncocytic nodules of renal parenchyma—is an extremely rare disorder with an incidence of about 4.3% of all solid renal masses. According to the literature, only four similar cases have been reported of oncocytosis with AO exposure, but there has been no definitive link. It is associated with CKD and Birt-Hogg-Dube syndrome. Diagnosis of RO remains challenging due to difficulty distinguishing between benign and malignant lesions with imaging. RO, in this case, could be related to CKD, and any link to previous exposure to AO will require further follow-up of patients with this history to determine if it is a risk factor for RO.